Work Safety Risk Analysis Using Hazard And Operability Study (Hazop) And Job Safety Analysis (Jsa) Methods In Cv. Xyz - Trisnayanti, Alivia Putri; Iriani, Yani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
CV XYZ is a company engaged in the production of fashion. The problem that occurs in CV XYZ is that there are still several cases of work accidents caused by the attitude of workers, the work environment and the tools used during the production process. The purpose of this study is to analyze the potential hazards and the causes of potential hazards, the risk of injury and even work accidents and provide suggestions for improvements to reduce the risk of work accidents so that control and prevention of hazards that arise in the work area can be carried out. The methods used in this research are Hazard and Operability Study (HAZOP) and Job Safety Analysis (JSA). Hazard and Operability Study (HAZOP) is a hazard identification approach in working environment conditions, existing facilities, equipment operation and overall production. Hazop looks for possible causes of accidents and determines the consequences of deviations that occur when a job is done. Job Safety Analysis (JSA) is the identification of hazards by taking into account unsafe act and unsafe conditions. This hazard identification method is carried out by studying a job to identify hazards and potential incidents associated with each step and used to find solutions and control existing hazards. Based on the results of data processing, it is known that the sources of hazards that exist or have the potential for work accidents are the attitudes of workers and the physical work environment and it is known that there are 30 identified hazards from 16 routine activities and 7 of them have the highest risk of intensity in causing hazards in the work area.